Epstein-Barr virus encoded microRNA BART7 regulates radiation sensitivity of nasopharyngeal carcinoma - Gao, Wei (Oncotarget, 2017)
Epstein-Barr virus (EBV)-associated nasopharyngeal carcinoma (NPC) is very sensitive to radiotherapy. To date, the underlying mechanism remains poorly understood. Here, we demonstrated that expression of EBV-encoded microRNA BART7 (ebv-miR-BART7) increases responsiveness of NPC to radiation treatment by targeting GFPT1/TGFβ1 signaling. GFPT1 is the the key rate-limiting enzyme of the hexosamine signaling pathway and governs TGFβ1 production. TGFβ1, a pleotropic cytokine with the potency to trigger self-renewal and damage-repair machinery in somatic cells. TGFβ1 can protect zebrafish embryo from the lethal effects of radiation treatment. In silico analysis showed that ebv-miR-BART7 could target GFPT1 transcript. Correlation analysis on primary NPC tissues suggested that ebv-miR-BART7 and GFPT1 have negative expression correlation. Expression of GFPT1 and TGFβ1 were inducible by radiation in NPC cell with ebv-miR-BART7 expression. Further, suppressing endogenous GFPT1 expression inhibited TGFβ1 which subsequently increased the responsiveness of NPC to radiation treatment. Taken together, our results demonstrated that ebv-miR-BART7 controls TGFβ1 production by targeting GFPT1. Detection of ebv-miR-BART7 may provide useful indicator for monitoring NPC progression and predict therapeutic outcomes.